Meet‐in‐the‐middle attacks on round‐reduced CRAFT based on automatic search - Zhangjun Ma; Manman Li; Shaozhen Chen (IET Information Security)
Abstract CRAFT is a lightweight block cipher designed by Beierle et al. to effectively resist differential fault attacks at fast software encryption 2019. In this article, Demirci‐Selçuk meet‐in‐the‐middle (DS‐MITM) attacks on round‐reduced CRAFT based on automatic search are proposed. A DS‐MITM automatic search model for CRAFT was constructed, and then, the automatic search model was used to detect a 9‐round DS‐MITM distinguisher. The strong relations between the round‐subtweakeys were observed and the key‐dependent sieve technique was adopted to reduce the memory complexity of the attack. Based on the 9‐round distinguisher, a 19‐round DS‐MITM attack can be presented. Due to the strong key relations, the time complexity can be reduced by the key‐bridging technique and the equivalent round‐subtweakey. The time complexity of the 19‐round DS‐MITM attack is 2114.68 19‐round CRAFT encryption, the data complexity is 256 chosen plaintexts, and the memory complexity is 2109 64‐bit blocks. Adding one round to the end of the 19‐round DS‐MITM attack, a 20‐round DS‐MITM attack can be proposed. The time complexity of the 20‐round attack is 2126.94 20‐round CRAFT encryption, the data complexity is 256 chosen plaintexts, and the memory complexity is 2109 64‐bit blocks.